Personality characteristics and individual factors associated with PTSD in firefighters one month after extended wildfires - Psarros, C; Theleritis, C; Kokras, N; Lyrakos, D.; Koborozos, A.; Kakabakou, O.; Tzanoulinos, G.; Katsiki, P.; Bergiannaki, JD (Nord J Psychiatry, 2018)
BACKGROUND: Firefighters participate in activities with intense physical and psychological stress and are constantly at risk to develop various psychopathological reactions. AIMS: To investigate psychological reactions in firefighters one month after devastating wildfires in Greece, during August 2007, which lead to the devastation of large areas and the death of 43 people among whom three were firefighters. METHODS: One month after the wildfires, a joint task force of mental health clinicians was organized in order to provide psychological support and to investigate the psychological consequences of wildfires to firefighters. One hundred and two firefighters, living within the fire-devastated area, who were on duty for the whole period of wildfires were interviewed and assessed with the use of several questionnaires and inventories. RESULTS: Post-traumatic stress disorder (PTSD) was detected in 18.6% of firefighters. Multiple logistic regression found that existence of fear of dying during firefighting, insomnia and increased scores in neuroticism, as well as in depression subscale of the SCL-90, were significantly associated with greater likelihood for having PTSD. Additionally those firefighters who worked permanently had 70% lower probability of having PTSD vs. those seasonally employed. CONCLUSIONS: Insomnia, depressive symptoms, as well as personality characteristics as neuroticism and the perception of fear of imminent death during firefighting operations may precipitate the development of PTSD in firefighters. Within this context, mental health clinicians should be aware that the early detection of these predisposing factors may facilitate the prevention and mitigation of PTSD in firefighters particularly those who are seasonally employed.
Keywords: *Individuality; *Personality; *Wildfires; Adult; Depression/diagnosis/epidemiology/psychology; depressive symptoms; fear of imminent death; Firefighters; Firefighters/*psychology; Greece/epidemiology; Humans; Insomnia; Male; Middle Aged; neuroticism; Ptsd; Sleep Initiation and Maintenance Disorders/diagnosis/epidemiology/psychology; Stress Disorders, Post-Traumatic/diagnosis/epidemiology/*psychology; Stress, Psychological/diagnosis/epidemiology/psychology; Surveys and Questionnaires; Time Factors